Streptococcus agalactiae em gestantes atendidas em uma maternidade pública: incidência e avaliação da sensibilidade a antimicrobianos - Nascimento, Gildevane Vieira (2016)
Streptococcus agalactiae or group B streptococci (GBS) can be part of the normal human flora and colonize the female genital tract. Thus, this bacterium can be transmitted to the infant during delivery and cause infections such as meningitis, sepsis, among others. This study aimed to assess the prevalence of GBS colonization in pregnant women cared in a public maternity in the capital of Piauí from May to August of 2014. It was evaluated 127 pregnant women between the 35th - 37th weeks of their pregnancy. It was analyzed 254 vaginal and anal secretions, which were collected and placed in Stuart transport medium and inoculated in Todd-Hewitt broth at 37 °C. After 24 hours, the samples were subcultured in broth grenade. The positive samples in grenade broth (yellow color) were plated on blood agar and incubated at 37 °C for 24 hours. The suggestive colonies were subjected to catalase test and gram staining. After the confirmatory test of latex agglutination, the sensitivity profile was determined. From the 127 pregnant women studied, 24.41% (31) had a positive culture for GBS, while 83.07% (96) were culture negative. It was found a total of 43 (16.93%) positive and 211 (83.07%) negative samples. There was a significant difference in positive results according to the anatomical site of collection, in which 12 women (9.45%) were positive at both sites, 12 (9.45%) in the vaginal site, and 7 (5.51 %) in the anal site. From the 43 positive samples, 4 (9.3%) were sensible and 32 (74.42%) resistant to erythromycin. In relation to clindamycin, 3 (6.98%) were sensible and 34 (79.07%) resistant. It was found in this study that the prevalence of GBS colonization in pregnant women surveyed agreed with the literature. The resistance profile was high, which shows the need for GBS research implementation in pregnant women as a form of prevention of newborn infection, and as a way to avoid the indiscriminate use of antibiotics that can lead to the emergence of resistant strains.